Of men and the ruling ring: Sri Lanka's executive presidency through Tolkien's trilogy - Perera, B. (Faculty of Law, University of Colombo, 2021)
In this paper, I read Sri Lanka's executive presidency through Tolkien's three-volume novel, the Lord of the Rings. I commence this interdisciplinary endeavour by using the Lord of the Rings story as an allegory to elucidate the extent of the hegemonic power accorded to the executive president by the Constitution of Sri Lanka 1978. For this purpose, I compare the nature of the power dynamics resulting from the executive presidency with that of the One Ring, which allows its wielder the power to overpower the novel's world. I draw parallels between their design and the effect upon those who possess them. However, the significance of delving into the nuances of this comparison between law and literature lies not only in its capacity to elucidate the current power dynamics of the executive presidency but also in its potential to pose an artistic challenge towards these power dynamics. The contribution of fantasy literature is especially important in this regard because the very function of the fantasy genre is to defy convention, defy the status quo, and imagine the impossible. Therefore, I approach fantasy literature also as a form of literary resistance. Focusing on law, the capacity to imagine new visions for justice plays a significant role in the development of the law itself. Therefore, I explore what the Lord of Rings can offer to further develop our vision regarding the executive presidency of Sri Lanka. With this aim, I interpret the novel's quest to destroy the ring as a saga ofpersistent resistance and apply this interpretation to the Sri Lankan attempts at abolishing and limiting the powers of the presidency so far.
Keywords: law and literature; fantasy fiction; hegemonic power; executive presidency; Sri Lanka